2018
DOI: 10.24042/ajipaud.v1i2.3741
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Kemampuan Membaca Permulaan Dengan Menggunakan Metode Bermain Flash Card Subaca

Abstract: This study aims to improve the ability to read the beginning of students by using the SUBACA Flash Card method for children in group B PAUD AL-ANISA Bentiring, Bengkulu City. This type of research is Classroom Action Research using two cycles, where each cycle is carried out in three meetings. Methods of collecting data in the form of observation and documentation. The results showed that there was an increase in reading the beginning of the child in each cycle with the average percentage of success in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Di belakang kartu juga tersaji panduan (guideline) & topik pembicaraan yang berkaitan dengan gambar di kartu serta adanya barcode yang akan mengarahkan ke video tutorial untuk memberikan rincian penggunaan kartu sebelum diberikan kepada anak. Hal ini berguna untuk membantu pembimbing (orangtua/pemberi stimulasi) dalam memainkan flashcard tersebut (Novita & Suyadi, 2020;Sari et al, 2018).…”
Section: Metodeunclassified
“…Di belakang kartu juga tersaji panduan (guideline) & topik pembicaraan yang berkaitan dengan gambar di kartu serta adanya barcode yang akan mengarahkan ke video tutorial untuk memberikan rincian penggunaan kartu sebelum diberikan kepada anak. Hal ini berguna untuk membantu pembimbing (orangtua/pemberi stimulasi) dalam memainkan flashcard tersebut (Novita & Suyadi, 2020;Sari et al, 2018).…”
Section: Metodeunclassified
“…Another study conducted by [25] also showed that VAKT results can improve the ability to read words of children with mild intellectual impairment The form of the VAKT approach in this study is a flashcard whose manufacture utilizes used cardboard and the letters are made of sandpaper, serves so that students can feel every letter they learn made from sandpaper, which has a function so that students can feel each letter by letter. According to [26] flashcards are visual learning media that are useful for making it easier for children to remember the learning process. Flashcards are considered to help facilitate children's vocabulary because they can process the right brain to remember objects seen.…”
Section: Icap-hmentioning
confidence: 99%
“…Ukuran dari Flash Card disesuaikan dengan kebutuhan kelas, maksudnya ukuran media Flash Card untuk kelas sempit akan berbeda dengan ukuran media Flash Card pada kelas yang luas dan anak didiknya banyak. (Partikasari et al, 2018) Media pembelajaran pada TK Sahabat Rina diantaranya susunan huruf a-z, angka 1-100 pada sisi ruangan kelas, beberapa tema yang ditempelkan pada dinding luar kelas seperti tema keluargaku, tubuhku dan lain sebagainya. Kegiatan pembelajaran membaca permulaan yang berlangsung di TK Sahabat Rina adalah guru menulis satu kata di papan tulis kemudian menyebutkan bunyi huruf dari kata tersebut.…”
Section: Pendahuluanunclassified